A novel mechanism for dissimilatory nitrate reduction to ammonium in Acididesulfobacillus acetoxydans - Reinier A. Egas; Julia M. Kurth; Sjef Boeren; Diana Z. Sousa; Cornelia U. Welte; Irene Sánchez-Andrea (mSystems, 2024)
ABSTRACTThe biological route of nitrate reduction has important implications for the bioavailability of nitrogen within ecosystems. Nitrate reduction via nitrite, either to ammonium (ammonification) or to nitrous oxide or dinitrogen (denitrification), determines whether nitrogen is retained within the system or lost as a gas. The acidophilic sulfate-reducing bacterium (aSRB) Acididesulfobacillus acetoxydans can perform dissimilatory nitrate reduction to ammonium (DNRA). While encoding a Nar-type nitrate reductase, A. acetoxydans lacks recognized nitrite reductase genes. In this study, A. acetoxydans was cultivated under conditions conducive to DNRA. During cultivations, we monitored the production of potential nitrogen intermediates (nitrate, nitrite, nitric oxide, hydroxylamine, and ammonium). Resting cell experiments were performed with nitrate, nitrite, and hydroxylamine to confirm their reduction to ammonium, and formed intermediates were tracked. To identify the enzymes involved in DNRA, comparative transcriptomics and proteomics were performed with A. acetoxydans growing under nitrate- and sulfate-reducing conditions. Nitrite is likely reduced to ammonia by the previously undescribed nitrite reductase activity of the NADH-linked sulfite reductase AsrABC, or by a putatively ferredoxin-dependent homolog of the nitrite reductase NirA (DEACI_1836), or both. We identified enzymes and intermediates not previously associated with DNRA and nitrosative stress in aSRB. This increases our knowledge about the metabolism of this type of bacteria and helps the interpretation of (meta)genome data from various ecosystems on their DNRA potential and the nitrogen cycle.IMPORTANCENitrogen is crucial to any ecosystem, and its bioavailability depends on microbial nitrogen-transforming reactions. Over the recent years, various new nitrogen-transforming reactions and pathways have been identified, expanding our view on the nitrogen cycle and metabolic versatility. In this study, we elucidate a novel mechanism employed by Acididesulfobacillus acetoxydans, an acidophilic sulfate-reducing bacterium, to reduce nitrate to ammonium. This finding underscores the diverse physiological nature of dissimilatory reduction to ammonium (DNRA). A. acetoxydans was isolated from acid mine drainage, an extremely acidic environment where nitrogen metabolism is poorly studied. Our findings will contribute to understanding DNRA potential and variations in extremely acidic environments.